Trio for two violins and viola, arrangement of the Trio for winds, op. 87, published by Artaria [ca. 1820] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Austria; Vienna; Artaria et Comp., 2024)
Parts for the Trio for two violins and viola, arrangement of the Trio in C major for two oboes and English horn, op. 87, later issue of the first edition published by Artaria in 1806, with later issue with price indication "1f. 18 x C.M." on title page.